How invention begins : echoes of old voices in the rise of new machines - Lienhard, John H., 1930- (Oxford University Press, 2006)
Invention--that single leap of a human mind that gives us all we create. Yet we make a mistake when we call a telephone or a light bulb an invention, says John Lienhard. In truth, light bulbs, airplanes, steam engines--these objects are the end results, the fruits, of vast aggregates of invention. They are not invention itself. In How Invention Begins, Lienhard reconciles the ends of invention with the individual leaps upon which they are built, illuminating the vast web of individual inspirations that lie behind whole technologies. He traces, for instance, the way in which thousands of people.